Adaptive beamforming based on theoretical interference-plus-noise covariance and direction-of-arrival estimation - Mohammadzadeh, Saeed; Kukrer, Osman (Inst Engineering Technology-Iet, 2018)
A simple and effective adaptive beamforming technique is proposed for uniform linear arrays, which are based on projection processing for covariance matrix construction and desired-signal steering vector estimation. The optimal minimum variance distortion-less response beamformer is closely achieved through approximating the interference-plus-noise covariance matrix by utilising the eigenvalue decomposition of the received signal's covariance matrix. Moreover, the direction-of-arrival (DOA) of the desired signal is estimated by maximising the beamformer output power in a certain angular sector. In particular, the proposed beamformer utilises the aforementioned DOA in order to estimate the desired-signal's steering vector for general steering vector mismatches. Simulation results indicate the better performance of the proposed method in the presence of the different errors compared with some of the recently introduced techniques.
Keywords: array signal processing; covariance matrices; direction-of-arrival estimation; interference (signal); vectors; eigenvalues and eigenfunctions; decomposition; direction-of-arrival estimation; adaptive beamforming technique; uniform linear array; covariance matrix construction; desired-signal steering vector estimation; optimal minimum variance distortionless response beamformer; interference-plus-noise covariance matrix; eigenvalue decomposition; received signal covariance matrix; DOA estimation